Identifying the Effective Factors of Promoting the Organizational Identiy of the Employees of the Country s Education System : A Meta-Comination Approach –Delphi - Karimi, Teyebeh; Farhangi, Ali Akbar; Moazzami, Mojtaba (Management Strategies and Engineering Sciences, 2024)
Organizational identity refers to the characteristics of an organization that define its essence and differentiate it from other organizations. It serves as a means to foster coherence, acts as a key element in organizational success, and is a fundamental aspect of organizational life as well as a critical dimension in the relationship between employees and the organization. In today's competitive landscape, leading organizations strive to attract professional and specialized potential employees and retain their human resources. A strong organizational identity can naturally contribute to employee retention and plays a significant role in improving job performance. Moreover, it guides employees towards efforts that support and advance organizational goals. Therefore, the objective of this research is to identify the factors influencing the enhancement of organizational identity among employees in the national education system. The research is descriptive-survey in nature and adopts a qualitative approach. This study was conducted in two phases. In the first phase, using a qualitative meta-synthesis method, the components of organizational identity were identified. In the second phase, these identified components were finalized using the Delphi method with input from 30 experts. A total of 56 prominent concepts were extracted, and through the Delphi method, 28 concepts were categorized into six main groups, including causal conditions of organizational identity, central phenomenon of organizational identity, organizational identity strategies, contextual (environmental) factors, intervening factors, and consequences of organizational identity.